PERILAKU KONSUMEN SAYURAN ORGANIK DI KOTA PEKANBARU - Ahmad Rifai; Didi Muwardi; Juwita Rizki Fitri Nauli Rangkuti (JIP ( Jurnal Industri dan Perkotaan ), 2008)
This research aimed to understanding the consumer attitudes on the organicvegetable attributes, and the influence of the consumer’s social environment toward thesubjective norm in the making the purchasing decision on the organic vegetable in Pekanbaru.Source of data was primary data from interview with respondents using purposive sampling.Method of analysis used Fishbein model to analysis the consumer’s attitudes and tounderstanding the consumer’s decision making process. The attributes was used tounderstanding the consumer’s attitudes is freshness, colour, taste, brand, ingredients,advantage for health, price and the availability. And the attribute was analyzed to analyzedthe influence of the consumer’s social environment is the product’s legal aspect and thefamily members. The research result showed that there was a positive attitude of consumer toconsume the organic vegetable. Attribute “the advantage of organic vegetable for health isowned the higher positive score to influence the consumer’s attitudes to consume the organicvegetable. And the social environment is not influence the subjective norm of consumer inmaking the purchasing decisions of the organic vegetables.